Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Profitabilitas Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024 - Wulan Amini Fitri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of capital structure and firm size on profitability with dividend policy as an intervening variable in mining sector companies listed on the Bursa Efek Indonesia during the 2020–2024 period. This research employs a quantitative approach using multiple linear regression and path analysis. The data were obtained from annual financial statements and processed using SPSS version 26. Profitability was measured by Return on Assets (ROA), capital structure by Debt to Equity Ratio (DER), firm size by the natural logarithm of total assets, and dividend policy by Dividend Payout Ratio (DPR). The results indicate that capital structure does not have a significant effect on dividend policy, while firm size has a significant effect on dividend policy. Capital structure significantly affects profitability; however, firm size and dividend policy do not have a significant effect on profitability. Furthermore, dividend policy is not able to mediate the effect of capital structure and firm size on profitability.